Analysis of Shrimp Pond Business Income in Farmer Groups in Tambaksumur Village, Tirtajaya Sub-District, Karawang - Putri, Dian Meiliya; Mulyadi, Dedi; Sandi, Santi Pertiwi Hari (West Science Business and Management, 2024)
Indonesia is the largest tropical marine country in the world and has the largest biodiversity in the sea. Abundant water resources can be fully optimized to meet human economic needs. The length of the coast of Karawang Regency reaches 84.32KM, which crosses nine districts, including Cilamaya Kulon, Cilamaya Wetan, Tempuran, Pedes, Cilebar, Cibuaya, Tirtajaya, Batujaya, and Pakisjaya. Based on the Regional Autonomy Law, the marine area of Karawang Regency has a limit of 4 miles from the lowest tide, so that the total area of the sea is estimated to be around 621.27KM2. Similarly, it is expected that the potential of ponds as part of the development of water areas, both at sea and on land, can be utilized by pond farmers. The purpose of this study was to analyze the income of shrimp pond business in the village of Tambak Sumur, located in Tirtajaya District of Karawang Regency (1) and to know how the shrimp pond farmers anticipate a decrease in income in the dry season (2). The method used in this study uses a qualitative descriptive method in which the data collection method used in this study uses primary data, which is obtained through direct interviews with respondents combined with questions. The results of income from 50%-90% indicate a loss or decrease in income that occurs when the prolonged dry season comes, because it is very influential on the growth of shrimp to be sold and each shrimp has a different price (1) and the Shrimp Pond Farmers To anticipate a decrease in income, the Shrimp Pond Farmers will look for shrimp in other places to sell back to the market so that the income of the pond farmers can continue to run (2).